Interleukin-13, Interleukin-10, Interferon-gamma and IDO Production in Response to Home Dust Mites in Allergic Asthma - Cityta Putri Kwarta; Heri Wibowo; Yordan Khaedir; Iris Rengganis; Hanny Siti Nuraeni (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Allergic asthma is a degenerative atopic disease caused by allergic or hypersensitivity type-1. More than 50% of people with allergic asthma are caused by the presence of house dust mites (HDMs) allergens.METHODS: The cellular immunity response was evaluated through a peripheral blood mononuclear cell (PBMC) culture isolated from blood, using the ficoll gradient technique. Subjects were atopic asthma groups and non-atopic asthma groups. PBMC from each subject cultured was stimulated with HDMs allergen, then incubated in a CO2 5% incubator, 37o C for 72 hours. With the multiplex assay method, interferon (IFN)-γ, interleukin (IL)-13 and IL-10 were measured, meanwhile indoleamine 2,3-dioxygenase level (IDO) was measured by the enzyme-linked immunosorbent assay (ELISA) sandwich methods.RESULTS: The IFN-γ production in the supernatant of PBMC cultures was stimulated by phytohemagglutinin (PHA), Roswell Park Memorial Institute (RPMI) medium and allergens. The IFN-γ production in allergen-stimulated supernatants showed higher level of IFN-γ in the nonatopic group (4,681,455±3,434,851) than atopic group (4,363,300±2,067,941) even though it was not statistically significant (p=0.078). There were no differences between the mean of IL-13 production in atopic asthma group and non-atopic group. The IL-10 production in allergenstimulated supernatants was shown to be higher in nonatopic group and were statistically significantly different (p=0.015). The IDO production in allergen-stimulated supernatants was shown to be higher in the non-atopic group (272,231±269,564) than in the actopic group (13,273±400), and it was significantly different (p=0.007).CONCLUSION: Cellular immune profile of subjects with allergic asthma to Dermatophagoides pterronyssinus (Der p) is characterized by a type-2 inflammatory response that is dominant compared to type-1 inflammation (higher IL-13 ratio compared to IFN-γ) and to the role of anti-inflammation (higher IL-13 ratio compared to IL-10). The decline in IDO production in allergic asthma subjects to Der p is thought to be related to the low cellular immune response in expressing IFN-γ compared to IL-13.KEYWORDS: interleukin-13, interleukin-10, IDO, PBMC, asthma